2021
DOI: 10.1080/20445911.2021.1890092
|View full text |Cite
|
Sign up to set email alerts
|

Learning to avoid biased reasoning: effects of interleaved practice and worked examples

Abstract: It is yet unclear which teaching methods are most effective for improving critical thinking (CT) skills and especially for the ability to avoid biased reasoning. Two experiments (laboratory: N = 85; classroom: N = 117), investigated the effect of practice schedule (interleaved/blocked) on students' learning and transfer of unbiased reasoning, and whether it interacts with practice-task format (worked-examples/problems). After receiving CT-instructions, participants practiced in: (1) a blocked schedule with wor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(20 citation statements)
references
References 91 publications
1
12
4
Order By: Relevance
“…Contrary to our expectations, we did not reveal pretest to posttest performance gains on learning items. Thus, we did not replicate the finding that participants' performance improves after explicit instructions combined with retrieval practice on domain-specific problems (Hypothesis 1: e.g., Heijltjes et al, 2015;Van Peppen et al, 2018;Van Peppen, Verkoeijen, Kolenbrander, et al, 2021). It should be noted, however, that this comparable level of posttest performance was attained in less time than pretest performance (i.e., prior to instruction/practice).…”
Section: Discussioncontrasting
confidence: 77%
See 2 more Smart Citations
“…Contrary to our expectations, we did not reveal pretest to posttest performance gains on learning items. Thus, we did not replicate the finding that participants' performance improves after explicit instructions combined with retrieval practice on domain-specific problems (Hypothesis 1: e.g., Heijltjes et al, 2015;Van Peppen et al, 2018;Van Peppen, Verkoeijen, Kolenbrander, et al, 2021). It should be noted, however, that this comparable level of posttest performance was attained in less time than pretest performance (i.e., prior to instruction/practice).…”
Section: Discussioncontrasting
confidence: 77%
“…Transfer is the process of applying one's prior knowledge or skills to related materials or some new context (e.g., Barnett & Ceci, 2002;Cormier & Hagman, 2014;Haskell, 2001;Perkins & Salomon, 1992;Salomon & Perkins, 1989). There are some insights into fostering transfer of CT-skills to isomorphic tasks (in this study referred to as learning; e.g., Heijltjes, Van Gog, Leppink, et al, 2014), but not into transfer to novel tasks that share underlying principles but have not been previously encountered (e.g., Heijltjes et al, 2015;Heijltjes, Van Gog, Leppink, et al, 2014;Van Peppen et al, 2018;Van Peppen, Verkoeijen, Kolenbrander, et al, 2021). As it is crucial that students can successfully apply the CT-skills acquired at a later time and to novel contexts/problems and it would be unfeasible to train students on each and every type of reasoning bias they will ever encounter, more knowledge is needed into the conditions that not only yield learning of CT-skills but also transfer.…”
Section: Introductionmentioning
confidence: 80%
See 1 more Smart Citation
“…These studies revealed that CT-skills of many higher education graduates are insufficiently developed (e.g., Arum & Roksa, 2011;Flores et al, 2012;Pascarella et al, 2011; although a more recent meta-analytic study reached the more positive conclusion that students' do improve their CT-skills over college years : Huber & Kuncel, 2016). Hence, there is a growing body of literature on how to teach CT (e.g., Abrami et al, 2008Abrami et al, , 2014Van Peppen et al, 2018, 2021Angeli & Valanides, 2009;Niu et al, 2013;Tiruneh et al, 2014Tiruneh et al, , 2016.…”
Section: Introductionmentioning
confidence: 99%
“…Previous research has shown that CT-skills required for unbiased reasoning consistently failed to transfer to novel problem types, i.e., far transfer, even when using instructional methods that proved effective for fostering transfer in various other domains (Van Peppen et al, 2018, 2021Heijltjes et al, 2014aHeijltjes et al, , 2014bHeijltjes et al, , 2015 this also applies to CT-skills more generally, see for example Halpern, 2014;Ritchhart & Perkins, 2005;Tiruneh et al, 2014Tiruneh et al, , 2016. This lack of transfer of CT-skills is worrisome because it would be unfeasible to train students on each and every type of reasoning bias they will ever encounter.…”
Section: Introductionmentioning
confidence: 99%